Fostering Environmental Awareness Through School-Based Programs: A Case Study of the Adiwiyata Initiative in Indonesian Elementary Education - Gancar Pramistri Ambawono; Budiono Budiono; Endang Poerwanti (AL-ISHLAH: Jurnal Pendidikan, 2025)
Environmental degradation remains a pressing issue globally and in Indonesia. School-based programs such as the Adiwiyata Initiative aim to instill environmental awareness and sustainable behaviors among students from an early age. However, the extent to which such programs influence behavior beyond school settings remains underexplored. This qualitative case study examined the implementation and impact of the Adiwiyata Program at SD Negeri Lowokwaru 5 Malang, Indonesia. Data were collected from 24 participants—including students, teachers, parents, and school administrators—through in-depth interviews, observations, and document analysis. Thematic analysis was conducted using Miles and Huberman’s interactive model. Findings revealed that the program effectively enhanced students’ environmental awareness and behaviors within the school context. Activities such as composting, recycling, and project-based learning fostered ecological responsibility. School leadership and teacher involvement were key drivers of success. However, behavior change at home was less consistent, primarily due to limited environmental literacy among parents and uneven support from families. The study highlights the potential of participatory, school-based environmental education to shape pro-environmental behavior. However, long-term sustainability requires stronger integration with family and community contexts. Parental training and cross-sector collaboration are recommended to reinforce environmental values beyond the classroom. While the Adiwiyata Program positively impacted students’ environmental habits at school, its influence at home was limited. Bridging this gap through community engagement and parental involvement is essential for fostering enduring environmental awareness in children.